THE ROLE OF LECTURES IN MODERN MEDICAL EDUCATION - Y. Budayev; O. Godovanets; O. Vakolyuk; S. Kostenyuk (Bukovynian State Medical University, 2019)
The purpose of the lecture is to cause a response from the audience mental activity. The task of lecture is to make the thinking active and fruitful. Lecture must remain in the memory of students and to develop further in the minds of listeners without the participation of the lecturer. Become a master of lecturing art - this is the great achievement in pedagogical career of a teacher.